Land preparation and field lay-out of Channels for Irrigation - satpute, R.V. (Journal of Soil and Water Conservation, 2022)
Irrigation is the surest source of successful farming and additional crop yields. Water can be made available from wells by lift and from canals by flow for irrigating crops. Digging irrigation wells or construction of reservoirs, tanks, canals and such other stru-ctures is a costly work. In general, the cost varies from Rs. 800/- to Rs. 10001- per acre irrigated. This valuable resource must be wisely used. The observation of' experts dealing with topic is, however, that this scarce commodity is used negligently and extravagantly through inefficient and wasteful methods of water utiliza-tion at the farm level. At least forty to fifty percent of the irrigation water which reaches farms either from wells or surface sources, is wasted.